Understanding the Physiopathology Behind Axial and Radial Diffusivity Changes—What Do We Know? - Winklewski, Pawel J.; Sabisz, Agnieszka; Naumczyk, Patrycja; Jodzio, Krzysztof; Szurowska, Edyta; Szarmach, Arkadiusz (Frontiers in Neurology, 2018)
The use of the diffusion tensor imaging (DTI) is rapidly growing in the neuroimaging field. Nevertheless, rigorously performed quantitative validation of DTI pathologic metrics remains very limited owing to the difficulty in co-registering quantitative histology findings with magnetic resonance imaging. The aim of this review is to summarise the existing state of the art knowledge with respect to axial (λ║) and radial (λ┴) diffusivity as DTI markers of axonal and myelin damage, respectively. Firstly, we provide technical background for DTI and briefly discuss the specific organization of white matter in bundles of axonal fibres running in parallel; this is the natural target for imaging based on diffusion anisotropy. Secondly, we discuss the four seminal studies that paved the way for considering axial (λ║) and radial (λ┴) diffusivity as potential in vivo surrogate markers of axonal and myelin damage, respectively. Then, we present difficulties in interpreting axial (λ║) and radial (λ┴) diffusivity in clinical conditions associated with inflammation, oedema, and white matter fibre crossing. Finally, future directions are highlighted. In summary, DTI can reveal strategic information with respect to white matter tracts, disconnection mechanisms, and related symptoms. Axial (λ║) and radial (λ┴) diffusivity seem to provide quite consistent information in healthy subjects, and in pathological conditions with limited oedema and inflammatory changes. DTI remains one of the most promising non-invasive diagnostic tools in medicine.